2010
DOI: 10.1186/1471-2180-10-140
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine inhibit biofilms produced by Pseudomonas aeruginosa

Abstract: BackgroundPseudomonas aeruginosa is a common pathogen in chronic respiratory tract infections. It typically makes a biofilm, which makes treatment of these infections difficult. In this study, we investigated the inhibitory effects of N-acetylcysteine (NAC) on biofilms produced by P. aeruginosa.ResultsWe found that minimum inhibitory concentrations (MICs) of NAC for most isolates of P. aeruginosa were 10 to 40 mg/ml, the combination of NAC and ciprofloxacin (CIP) demonstrated either synergy (50%) or no interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
180
4
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(210 citation statements)
references
References 26 publications
13
180
4
13
Order By: Relevance
“…Sonication was capable of detaching more bacteria than the NAC and scraping methods, thus confirming the usefulness of this method reported in clinical studies [4,12,23,[28][29][30]. Some studies [2,10,16,26,33] have shown that NAC alone or in combination with other compounds has strong activity against bacterial biofilm, and the mechanism involving the disruption of biofilm may induce the susceptibility of bacteria during antibiotic Fig. 9A-H Confocal laser scanning microscopy shows the formation and removal of biofilms on prosthetic materials for S aureus on PE discs (Stains: bacteria were stained green by Syto-9, the biofilm matrix was stained red by FilmTracer TM SYPRO Ruby Matrix Stain; original magnification, x 3000).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Sonication was capable of detaching more bacteria than the NAC and scraping methods, thus confirming the usefulness of this method reported in clinical studies [4,12,23,[28][29][30]. Some studies [2,10,16,26,33] have shown that NAC alone or in combination with other compounds has strong activity against bacterial biofilm, and the mechanism involving the disruption of biofilm may induce the susceptibility of bacteria during antibiotic Fig. 9A-H Confocal laser scanning microscopy shows the formation and removal of biofilms on prosthetic materials for S aureus on PE discs (Stains: bacteria were stained green by Syto-9, the biofilm matrix was stained red by FilmTracer TM SYPRO Ruby Matrix Stain; original magnification, x 3000).…”
Section: Discussionsupporting
confidence: 73%
“…Sonication of explanted implants has notably improved sensitivity of microbiologic diagnosis of PJIs by dislodging bacteria from biofilm adhered to prosthetic surfaces, as documented in numerous studies [1,4,12,13,23,[28][29][30]. Since NAC exerts activity against bacterial biofilms [2,10,16,26,33], we presumed NAC and DTT could be used to remove bacteria from a prosthetic biofilm. We asked the following questions: (1) Do DTT and NAC remove bacteria from biofilm formed on prosthetic materials?…”
Section: Discussionmentioning
confidence: 97%
“…For characterizing anti-biofilms activity, the most common practice has been to use a single type of assay that measures reduction of total biomass or cellular viability 4,5 with less emphasis put into combining the three assays. 6 One likely explanation is that, to measure the EPS content, most of the available methods depend on the extraction of polysaccharides, 7,8 which makes them more laborious and time-consuming for anti-biofilm susceptibility studies.…”
Section: Introductionmentioning
confidence: 99%
“…Препарат приводит к уменьшению образования биопленок грам-положительными и грамотрицательными бактериями и грибами; уменьшает продукцию экстрацеллюлярного полисахаридного матрикса, что способствует разруше-нию зрелых биопленок [43][44][45]. Видимо, ацетилцистеин может разрушать дисульфидные связи бактериальных энзимов, воздействуя на главный компонент матрикса биопленки -экзополисахариды, участвующие в их обра-зовании или экскреции, и благодаря антиоксидантным свойствам, влиянию на метаболизм бактериальных кле-ток может нарушать функционирование адгезивных про-теинов бактерий [44], что подтверждено культуральным методом и электронной микроскопией [45].…”
Section: обзор литературыunclassified